Anthropological Shift? EU Human Rights’ Anthropology in View of Life and Family - Gierycz, Michal (Prudentia Iuris, 2020)
The article reveals and explains the change in the way of proclaiming the protection of human life and right to marry/found a family in the Charter of Fundamental Rights of the EU compared to the Universal Declaration of Human Rights and the European Convention on Human Rights. The Author verifies the thesis according to which that change is, at its roots, connected with an anthropological shift.